2013
DOI: 10.1002/oby.20595
|View full text |Cite
|
Sign up to set email alerts
|

Obesity status of middle school students in Xiangtan and its relationship with Internet addiction

Abstract: Objective: To investigate the state of middle school students' obesity in Xiangtan, China and to study the influence of Internet addiction on obesity. Subjects: 1,150 junior and senior middle school students in Xiangtan, China. Design and Methods: The research subjects were select randomly for the study. The height and body weight of human body were measured and the obesity state was judged according to BMI value and the Working Group on Obesity in China (WGOC) standard. The questionnaire for the survey of mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 16 publications
(26 reference statements)
4
26
1
1
Order By: Relevance
“…In the current study, 86% of the female students were normal Internet users that is consistent with the results of Seyrek et al (2017); Munno et al (2017); Hamidi, Mahdiyeh Najafabadi & Namazian Najafabadi (2015); and Rouhani & Tari (2011). However, it is contrary to the findings of Chen et al (2016) who reported an Internet addiction of 8.7% among Chinese adolescents, and Li et al (2014) who found that middle school students' Internet addiction in China was 21.13%. This discrepancy could be associated with differences in culture, the questionnaires, and study sample.…”
Section: Discussioncontrasting
confidence: 85%
“…In the current study, 86% of the female students were normal Internet users that is consistent with the results of Seyrek et al (2017); Munno et al (2017); Hamidi, Mahdiyeh Najafabadi & Namazian Najafabadi (2015); and Rouhani & Tari (2011). However, it is contrary to the findings of Chen et al (2016) who reported an Internet addiction of 8.7% among Chinese adolescents, and Li et al (2014) who found that middle school students' Internet addiction in China was 21.13%. This discrepancy could be associated with differences in culture, the questionnaires, and study sample.…”
Section: Discussioncontrasting
confidence: 85%
“… indicated an association between IA and BMI in healthy adolescents, and Li et al . also reported higher obesity rates in middle school students with IA than those without IA in this context. Common hedonic mechanisms may underlie obesity and addiction.…”
Section: Introductionmentioning
confidence: 52%
“…However, Li et al . examined the obesity status of middle school students and its relationship with IA. They found higher rates of obesity in students with IA than in students without IA suggesting that IA was an independent risk factor of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…and approximately 21.8% of Korean adolescents have been found to overuse computers for gaming (> 3 hours per day) [14]. Internet overuse may lead to several psychological problems, including depression, attention deficit hyperactivity disorder (ADHD), daytime sleepiness, and self-injurious behaviour [1520]; additionally, overuse of the internet has been related to detrimental physical health conditions, such as obesity [21,22]. Problematic internet use has been suggested to be related to lower school grades [22].…”
Section: Introductionmentioning
confidence: 99%